2021
DOI: 10.1177/23210222211024380
|View full text |Cite
|
Sign up to set email alerts
|

Do Share Repurchases Distort Stock Prices? Evidence from the United States and Malaysia

Abstract: Heavy share buyback years after the global finance crisis 2008–2009 drew criticism from scholars and financial press that share repurchases were being used by firms to manipulate their stock prices. This paper examines whether a greater firm’s repurchase intensity distorts stock prices reflecting to information. We analyse 2 sets of unbalanced panel data that contain a sample of 337 US and another sample of 167 Malaysian repurchasing firms between 2012 and 2016. Contrary to the criticism, we find that a greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In the United States, share repurchases can be used as a signalling tool and price support to help stock prices become more efficient, and share repurchases have no effect on stock prices in Malaysia (Chee et al, 2021). Jena et al (2020) investigated the determinants of share buyback choice in India for 430 buybacks and found that tender-offer and open-market buybacks are not close substitutes for one another that these two widely used methods serve different purposes for companies in India, and that companies should choose the repurchase method based on the buyback's purpose.…”
Section: Magnitude Of Share Repurchasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, share repurchases can be used as a signalling tool and price support to help stock prices become more efficient, and share repurchases have no effect on stock prices in Malaysia (Chee et al, 2021). Jena et al (2020) investigated the determinants of share buyback choice in India for 430 buybacks and found that tender-offer and open-market buybacks are not close substitutes for one another that these two widely used methods serve different purposes for companies in India, and that companies should choose the repurchase method based on the buyback's purpose.…”
Section: Magnitude Of Share Repurchasesmentioning
confidence: 99%
“…Doan et al (2011) emphasize that if a company feels a significant takeover danger, it will boost its on-market share buyback activity. The notion that share repurchase acts as a price support and signalling mechanism to encourage more efficient stock pricing has been supported by Chee et al (2021). Undervaluation is the primary reason for going for share repurchases.…”
Section: Introductionmentioning
confidence: 99%